Pengaruh Budgetary Goal Characteristics Terhadap Kinerja Pemerintah Daerah Kabupaten Muara Enim - Putri Velli Asri; Isni Andriana; Kemas M. Husni Thamrin (UNIVED Press, 2022)
The purpose of this study was to determine and analyze the Effect of Budgetary Goal Characteristics (Budget Goal Setting, Clarity of Budget Objectives, and Budget Evaluation) on the Performance of the Muara Enim Regency Government. The number of samples taken is 50 local government employees who have activities in budgeting and at the same time as budget implementers who handle budget preparation at the Muara Enim Regency government office as respondents. The data used is primary data, namely data taken from a questionnaire (questionnaire). The data analysis method used is a simple linear regression analysis method. The analysis data was processed using the SPSS (Sold Product Solution Statistics) computer program version 23. The results of this study stated that participation in budget preparation and budget evaluation had a significant positive effect, while the clarity of budget objectives had no significant effect on the performance of the local government of Muara Enim Regency.